Improving the mechanical properties of collagen‐based membranes using silk fibroin for corneal tissue engineering. Issue 3 (15th July 2014) - Long, Kai; Liu, Yang; Li, Weichang; Wang, Lin; Liu, Sa; Wang, Yingjun; Wang, Zhichong; Ren, Li
Abstract Although collagen with outstanding biocompatibility has promising application in corneal tissue engineering, the mechanical properties of collagen‐based scaffolds, especially suture retention strength, must be further improved to satisfy the requirements of clinical applications. This article describes a toughness reinforced collagen‐based membrane using silk fibroin. The collagen‐silk fibroin membranes based on collagen [silk fibroin (w/w) ratios of 100:5, 100:10, and 100:20] were prepared by using silk fibroin and cross‐linking by 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide. These membranes were analyzed by scanning electron microscopy and their optical property, and NaCl and tryptophan diffusivity had been tested. The water content was found to be dependent on the content of silk fibroin, and CS10 membrane (loading 10 wt % of silk fibroin) performed the optimal mechanical properties. Also the suture experiments have proved CS10 has high suture retention strength, which can be sutured in rabbit eyes integrally. Moreover, the composite membrane proved good biocompatibility for the proliferation of human corneal epithelial cells in vitro. Lamellar keratoplasty shows that CS10 membrane promoted complete epithelialization in 35 ± 5 days, and their transparency is restored quickly in the first month. Corneal rejection reaction, neovascularization, and keratoconus are not observed. The composite films show potential for use in the field of corneal tissue engineering. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1159–1168, 2015.